Influence of electrical discharge machining process parameters on surface micro-hardness of titanium alloy - Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Yeakub Ali , Mohammad (Institution of Mechanical Engineers, 2013)
The resistance of a material to an indentation on microscopic scale is an indication of its micro-hardness. To a lubrication engineer, micro-hardness is synonymous with surface wear resistance of a material. In this study, an attempt was made to enhance the surface micro-hardness of titanium alloy (Ti-6Al-4V) through modification of electrical discharge machining process parameters. These parameters are the electrode, the dielectric fluid and the electrical variables of the machine. Cu–TaC composite electrode produced through powder metallurgy method was used during the electrical discharge machining with different urea concentrations in distilled water as dielectric fluid. The electrical variables used were the peak current, the pulse duration and the duty factor. Electrical discharge machining was also conducted with copper (Cu) powder metallurgy electrode with distilled water dielectric fluid for comparison. The results showed that the micro-hardness of the electrical discharge machined surfaces with Cu–TaC electrode/urea dielectric fluid was generally higher than that of those with Cu electrode/distilled water dielectric fluid. The highest micro-hardness of 1795 Hv was attained with 10 g/L of urea concentration.